Rediscovery of Ophiorrhiza radicans (Rubiaceae) from the Western Ghats of Peninsular India - Joseph, Ginu; Hareesh, V. S.; Sreekumar, V. B.; Hrideek, T. K. (Rheedea, 2013)
Ophiorrhiza radicans Gardn. was rediscovered from Shenduruney Wild Life Sanctuary, Western Ghats of Kerala region after a lapse of 120 years. A detailed taxonomic description and illustration of this species is provided for easy identification.